Effective advertising to promote silat for young generations / Md Helmyshah Md Parlan - Md Parlan, Md Helmyshah (Faculty of Art and Design, 2013)
An effective advertising method to promote silat for young generation is really important to increase the number of participation. Lack of awareness and knowledge about silat influence young generations do not get involve in silat. From the project, the researcher comes out with an effective advertising medium and method to promote silat to the young generation. The objectives of this research are to identify the level of knowledge of young generation related to silat and to identify the effective advertising to promote silat for young generation. The target audiences for this research are students from primary and secondary school at Shah Alam. From the findings, researcher comes with the recommendations that will improve the level of knowledge about silat among young generations and the effective advertising and promotion to influence young generation to participate in silat.